PENGEMBANGAN PENGELOLAAN PUSAT SUMBER BELAJAR - sim, Erikson (IN VERITATE LUX, 2019)
This article aims to find out learning resource centers, the objectives and functions of learning resource centers, steps to develop learning resource centers, and how to manage learning resource centers. Learning resources are everything that learning is used to help students learn. The aim of the learning resource center is to increase the effectiveness and efficiency of teaching and learning activities through developing learning systems. The function of learning resources is as instructional, informational, media service, and administrative. Developing a Learning Resource Center can be done by: needs analysis, design, production, testing and production. Management of learning resource centers can be done by managing learning resources, namely that learning resource centers are able to overcome deficiencies and limitations in existing media supplies and improve learning outcomes so that they need to be equipped with procurement, development, production, training and services in their use